Prevalence and Management of Severe Hand, Foot, and Mouth Disease in Xiangyang, China, From 2008 to 2013 - Liu, Jian; Qi, Jing (Frontiers in Pediatrics, 2020)
Therapeutic strategies for severe hand, foot, and mouth disease (HFMD) are currently either inconsequent or deficient in evidence. We retrospectively surveyed HFMD outbreaks in Xiangyang from June 2008 to December 2013. HFMD is staged from I to V according to clinical severity. Severe HFMD is defined as a case involving central nervous system (CNS). We analyzed risk factors for fatality of severe cases and compared the efficiency and outcome of some therapies by binary logistic regression. The overall HFMD cases included 637 (1.26%) severe cases, 38 fatalities (0.075%). Analyses indicate that age (<3 y), enterovirus 71 (+), autonomic nervous system dysregulation, pulmonary edema/hemorrhage, CRP (>40 mg/L) and cardiac troponin I (>0.04 ng/mL) are risk factors for fatality (all P < 0.05). Intravenous immunoglobulin (IVIG) and mechanical ventilation applied only in early stage IV significantly improved HFMD progression (both P < 0.05) with odds ratios of 0.24 (95% CI: 0.10-0.57) and 0.01 (95% CI: 0.00-0.10), respectively. Neither methylprednisolone nor milrinone administered in any stage made any significant difference on mortality (all P > 0.05). Precise recognition of the severe HFMD cases in early stage IV and prompt IVIG and mechanical ventilation application may reduce mortality. Mechanical ventilation training programs and dispatch of specialists to hospitals where there is no chance of transferring critical cases to the severe HFMD designated hospitals are two key measures to reduce fatality.